Application of several novel natural antioxidants to inhibit oxidation of tree peony seed oil - Zhangzhen Bai; Rui Yu; Jian Li; Ning Wang; Yao Wang; Lixin Niu; Yanlong Zhang (CyTA - Journal of Food, 2018)
Tree peony seed oil (TPSO) is novel edible oil enriched in omega-3 polyunsaturated fatty acid. To inhibit TPSO oxidation, several individual and combined natural antioxidants were added and evaluated by peroxide value, DPPH and ABTS radical scavenging capacity under accelerated storage condition. The effects were also compared with synthetic antioxidants. We found that all the natural compounds have certain antioxidant effect at different concentrations, especially tea polyphenols (TP) that significantly prevented TPSO from oxidation at the concentration of 0.04%. Additionally, composite antioxidants significantly improved antioxidant effects, especially synergist ascorbyl palmitate (AP) was added. The composite 0.02% TP + 0.01% DMY (dihydromyricetin) + 0.01% AP exhibited the most effective inhibition effect on TPSO oxidation and strongest DPPH and ABTS radical scavenging capacity. These results demonstrated that the candidates individual and combined natural antioxidants are beneficial for lipid stabilization and health promotion, which are desirable substitutes for synthetic antioxidants.